Blood sampling: two sides to the story - Pickup, Laura; Atkinson, Sarah; Hollnagel, Erik; Bowie, Paul; Gray, Sandra; Rawlinson, Sam; Forrester, Kate (Elsevier, 2017)
This study aimed to investigate why there is variability in taking blood. A multi method Pilot study was completed in four National Health Service Scotland hospitals. Human Factors/Ergonomics principles were applied to analyse data from 50 observations, 15 interviews and 12-months of incident data from all Scottish hospitals. The Functional Resonance Analysis Method (FRAM) was used to understand why variability may influence blood sampling functions. The analysis of the 61 pre blood transfusion sampling incidents highlighted limitations in the data collected to understand factors influencing performance. FRAM highlighted how variability in the sequence of blood sampling functions and the number of practitioners involved in a single blood sampling activity was influenced by the working environment, equipment, clinical context, work demands and staff resources. This pilot study proposes a realistic view of why blood sampling activities vary and proposes the need to consider the system’s resilience in future safety management strategies.